Challenges of Home Care in Iran: A Focus on the Functions of the Health System - Mohanna Rajabi (International Journal of Community Based Nursing and Midwifery, 2023)
Home care, as a new form of healthcare services, is extending all over the world. This care is providedat the patients’ homes with the assistance and interaction between caregivers, patients, and families.Home care services include 24hr care, monitoring patient conditions, training medication uses, painmanagement, physiotherapy, speech therapy, parenteral nutrition, training patients and their families,and other similar services. In addition to reducing the imposed costs on patients and health systems,home care as an alternative to some hospital services, enhances the patients and their families’satisfaction, shortens the length of hospital stay, and reduces the problems associated with the presenceand hospitalization of patients in hospitals.1